Clinical and Spectral-Domain Optical Coherence Tomography Findings of Patients with Incomplete Visual Recovery after Anatomically Successful Retinal Detachment Surgery - Miltiadis K. Tsilimbaris; Aikaterini Chalkia; Chrysanthi Tsika; Anastasios Anastasakis; Georgios A. Kontadakis (Journal of Ophthalmology)
Purpose. To identify causes of incomplete visual recovery in patients with anatomically successful retinal detachment surgery. Methods. This was a retrospective study of 61 eyes of 61 patients with at least 12-month follow-up and complete preoperative, intraoperative, and postoperative record. Postoperative visual acuity (VA) more than 0.18 logMAR was considered as incomplete visual recovery. Complete ophthalmic examination and Spectral-Domain OCT (SD-OCT) imaging were performed at last follow-up. Results. Twenty-nine eyes (47.5%) had a postoperative VA < 0.18 logMAR and 32 eyes (52.5%) had a postoperative VA ≥ 0.18 logMAR. Mean follow-up was 32.8 ± 17.3 months. Incomplete visual recovery was strongly correlated with presence of macular pathology (P = 0.002), a detached macula preoperatively (P = 0.02), retinotomy (P = 0.025), and pars plana vitrectomy and use of silicon oil as a tamponade agent (P = 0.009). Also, although there was a strong correlation between ellipsoid zone disruption and incomplete visual recovery, a distinct, more course pathology could be identified in all cases of poor visual recovery related to edema, thickening, or atrophy of the macula. Conclusion. The careful postoperative evaluation of the macula using biomicroscopy and SD-OCT can help in diagnosis of alterations that can be associated with incomplete visual recovery.